Redesign of the production layout based on Chronoanalysis and Lean Manufacturing: case study in a metal-mechanical industry - Silva, Misael Yuri Inácio; Santos, João Evangelista Dantas dos; Santos, Rodolfo de Sousa (Brazilian Journal of Production Engineering, 2025)
he inadequate arrangement of equipment and sectors in a manufacturing environment can significantly compromise the efficiency of production processes. This article presents a case study of a metalworking company, whose objective was to optimize the production layout by applying chronoanalysis, quality tools and Lean Manufacturing principles. The investigation began with a detailed mapping of the steps involved in the production of two key parts, called “male” and “female”, totaling 73 operations analyzed. The data collected allowed the identification of bottlenecks, excessive movements and activities that did not add value to the final product. Based on this, the proposal was to reorganize the layout in a “U” shape, reconfigure internal flows and adopt standardization and visual management practices. The implementation of the improvements resulted in reduced manufacturing time, increased productivity, better use of physical space and reduced waste. The analysis of the heat map confirmed the effectiveness of the intervention by highlighting the elimination of critical movement zones. The results demonstrate that the integrated use of production engineering approaches can generate significant impacts on the operational efficiency of micro and small industries.
Keywords: Productive Layout; Chronoanalysis; Lean Manufacturing; Metalworking Industry; Process Optimization